2021
DOI: 10.1055/s-0041-1723057
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil-to-Lymphocyte Ratio and Platelet-to-Lymphocyte Ratio and Their Role as Predictors of Disease Severity of Coronavirus Disease 2019 (COVID-19)

Abstract: Context Due to the wide spectrum of clinical illness in coronavirus disease 2019 (COVID-19) patients, it is important to stratify patients into severe and nonsevere categories. Neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) have been evaluated rapidly by a few studies worldwide for its association with severe disease, but practically none have been conducted in the Indian population. This study was undertaken to examine the role of NLR and PLR in predicting severe disease in Indian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 13 publications
1
10
0
Order By: Relevance
“…However, the findings were consistent with previous studies that state an increase in PLR as an independent indicator of COVID-19 infection in the general population [Chan AS, Rout, A., 2020]. Moreover, several studies related to the severity indicator of COVID-19 stated that PLR was positively corresponds to the severity of the sufferer [Goh BKP et al, 2016;Chan AS, Rout, A., 2020;Jain R et al, 2021].…”
Section: Demographic Characteristics Of the Patientssupporting
confidence: 90%
“…However, the findings were consistent with previous studies that state an increase in PLR as an independent indicator of COVID-19 infection in the general population [Chan AS, Rout, A., 2020]. Moreover, several studies related to the severity indicator of COVID-19 stated that PLR was positively corresponds to the severity of the sufferer [Goh BKP et al, 2016;Chan AS, Rout, A., 2020;Jain R et al, 2021].…”
Section: Demographic Characteristics Of the Patientssupporting
confidence: 90%
“…An AUC of 0.779, with a larger OR of 1.237 and a cut-off of 4.1 showed 69% sensitivity and 78% specificity in predicting severe disease. The cut-off for PLR was 115.3, which showed 79% sensitivity and 62% specificity in predicting severe disease [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Severity was also predicted by NLR >4.93 (Turkey), >8.78 (Pakistan) and >5 (Iran) [8][9][10]. Different single centre studies from India suggested NLR of >3.3 predict progression of the disease, >5.2 for admission to ICU and >5.59 in severe COVID-19 disease [11][12][13]. Mechanical ventilation was required when NLR was >4.6 [14].…”
Section: Discussionmentioning
confidence: 99%
“…An initial PLR of 160 is associated with an adverse outcome which is concomitant to the study by Yang et al [ 7 ], and a peak PLR of 400 predicts mortality. Studies from other centres reveal a PLR of 180 (China and India), and 204 (India) [ 7 , 11 , 13 ]. The neutrophil and lymphocyte percentages were analysed in this study as many laboratories do not report absolute count, especially in resource-constrained areas.…”
Section: Discussionmentioning
confidence: 99%